2019
DOI: 10.1177/0972262919850920
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Effects of Financial Services Advertising on Financial Product Purchase: An Empirical Validation

Abstract: The main aim of the study is to find the effect of the financial advertisement on the respondent’s information selection, processing and analysing it while making the financial purchase decisions. The study identified the important factors that affect the investment decision-making process and explored them by using the exploratory factor analysis. The conceptual model has been tested using the AMOS SEM software. The factor analysis identified the four important factors that are affecting the financial decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 81 publications
1
1
1
Order By: Relevance
“…These results support previous research which states that there is no significant effect of celebrity endorsement on purchase intentions due to several reasons such as the ability of celebrities who are not able to communicate the value of the product and the distrust of customers because they feel that the celebrity is not an expert in the product being delivered (Dogra and Sharma, 2019;Martínez-lópez et al, 2020). Marketers who use celebrities need to consider content that is following product characteristics so that it can be effective in influencing customer purchase intentions.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…These results support previous research which states that there is no significant effect of celebrity endorsement on purchase intentions due to several reasons such as the ability of celebrities who are not able to communicate the value of the product and the distrust of customers because they feel that the celebrity is not an expert in the product being delivered (Dogra and Sharma, 2019;Martínez-lópez et al, 2020). Marketers who use celebrities need to consider content that is following product characteristics so that it can be effective in influencing customer purchase intentions.…”
Section: Resultssupporting
confidence: 86%
“…The customer also feels more natural and more comfortable when the product is presented by celebrities (Kusumasondjaja and Tjiptono, 2019;Loureiro and Sarmento, 2019). The results are in contrast to the previous one which stated that celebrities did not affect the customers' purchase intention because they are not considered as an expert, cannot judge certain products, and is necessary to have a special ability to give opinions (Dogra and Sharma, 2019;Martínez-lópez et al, 2020). Based on the gap of the previous research, this study offers other variables to get clear results and complete the research gap that is by adding brand trust as the moderator variable.…”
contrasting
confidence: 81%
“…To strive in India, managers should identify the essential financial advertisements antecedents influencing millennials' investment intentions (Dogra and Sharma 2019 ; Acar and Temiz 2017 ). Various researchers, such as Chalise and Anong ( 2017 ), Horner et al ( 2016 ) and Xiao et al ( 2011 , 2014 ), have identified different advertisement antecedents that affect consumer attitude and investment intention.…”
Section: Introductionmentioning
confidence: 99%